TM4SF1 Regulates Pancreatic Cancer Migration and Invasion In Vitro and In Vivo - Jia Cao; Jia-chun Yang; Vijaya Ramachandran; Thiruvengadam Arumugam; De-feng Deng; Zhao-shen Li; Lei-ming Xu; Craig D. Logsdon (Cellular Physiology and Biochemistry, 2016)
Background/Aims: The cell surface protein transmembrane 4 L6 family member 1 (TM4SF1) has been detected in various tumors and plays a major role in the development of cancer. We aimed to investigate the effects of TM4SF1 on the migration and invasion of pancreatic cancer in vitro and in vivo and explore its related molecular mechanisms. Methods: qRT-PCR and immunohistochemical analyses were used to measure the expression of TM4SF1 in pancreatic cancer tissues and adjacent tissues. TM4SF1 was silenced using siRNA and shRNA to investigate the role of this protein in the proliferation and metastasis of pancreatic cancer cells. MTS and Transwell assays were used to examine the effect of TM4SF1 on pancreatic cancer cell lines. The expression and activity of MMP-2 and MMP-9 were determined by qRT-PCR, western blots and gelatin zymography. In vivo, orthotopic pancreatic tumor models were used to examine the formation of metastasis. Results: qRT-PCR and immunohistochemical analyses showed that TM4SF1 was highly expressed in pancreatic cancer tissues compared with the adjacent tissues. In in vitro experiments the silencing of TM4SF1 reduced cell migration and invasion and down-regulated the expression and activity of MMP-2 and MMP-9. However, no significant difference in cell proliferation was detected after silencing TM4SF1. Additionally, knocking down TM4SF1 decreased the formation of lung and liver metastases in orthotopic pancreatic tumor models. Conclusion: Our results demonstrate that the expression of TM4SF1 is higher in pancreatic cancer tissues and pancreatic cancer cell lines than controls. Knockdown of TM4SF1 inhibited the migration and invasion of pancreatic cancer cells by regulating the expression and activity of MMP-2 and MMP-9, which suggests that TM4SF1 may play a significant role in metastasis in pancreatic cancer.